Women and Legal Hierarchy - Margaret Thornton (Legal Education Review)
Catharine MacKinnon mentioned that there were a number of conditions which would have to be met before feminism in legal education had been achieved. She mentioned, for example, the representation of women’s point of view, proportionality between male and female professors and between female and male secretaries. I am not very optimistic about the achievement of those conditions. I am not hopeful because I believe that the idea of feminism and law is an oxymoron. Women’s association with affectivity and desire prevents our acceptance as equals within the academy which is perceived as the quintessential locus of reason. Australian legal education has accepted this assignation of men and women to separate spheres and, even though the proportion of women students is now around 50 per cent, which is indeed characteristic of legal education throughout the English-speaking world, I think that this has made relatively little difference, either in terms of substance or process.